MARKETING STRATEGY OF AGRICULTURAL PRODUCTS BY UTILIZING SOCIAL MEDIA IN KELAMBIR LIMA KEBUN VILLAGE, HAMPARAN PERAK DISTRICT, DELI SERDANG REGENCY - Hidayati Purnama Lubis (CERED Indonesia Institute, 2021)
Indonesia as one of the countries that produce a lot of agricultural products, one of them is Labu Kuning fruit (Cucurbita moschata), which is quite easy in various places in Indonesia such as in Kelambir Lima Kebun, District Hamparan Perak, Deli Serdang regency which becomes an ingredient to be processed and used as a snack finished product such as diamonds and crackers. The processed products have the opportunity to become a source of income for the people in the village and reduce the number of unemployed. Community service is implemented aimed at providing solutions that provide counseling to community groups consisting of Housewives and Youth, how to market and sell products that have been produced can compete in the market by using social media, with the ultimate goal of increasing income and welfare of the household.